Emerging Labor Conflict and Politicity in Pandemic-Hit Argentina - COLLADO, Patricia; ROITMAN, Susana (Utopía y Praxis Latinoamericana, 2024)
Our research analyzes emerging labor conflict in pandemic-hit Argentina as well as its aftermath. Our hypothesis is that, albeit state mandated social distancing and controls, the workers partially rebuffed their “social designated roles in the pandemic” along with imposed work conditions. Whenever possible the workers organized themselves to resist independently of union leadership and in spite of the limits to protest in public spaces. In order to understand this process, we think in terms of multiple temporalities and spatial levels, all leading to the time of the pandemic event and intend to gain insight in the emerging subjects and organizational forms. Our focus is on Cordoba’s health workers conflict of 2022, to show in a case study the inflection that the pandemic brought about. Our sources are different international, national and provincial databases as well as testimonies to said conflict.